THE EFFECT OF NON-FINANCIAL REWARD AND PUNISHMENT ON JOB LOYALTY THROUGH JOB SATISFACTION - Ida Nyoman Basmantra (Jurnal Ilmiah Manajemen & Bisnis, 2018)
The effect of non-financial reward and punsihment on job loyalty through job satisfaction. The objectives of this research is to study the effect of non-financial reward, punishment, and job satisfaction on job loyalty, this research was conducted at Atta Mesari Resort and Spa. The data collection technique used in this research was questionnaire, the questionnaire used in this research had been tested and is considered valid and reliable. in order to measure the effect of non-financial reward, punishment, and job satisfaction and the effect on job loyalty this research used the multiple regression analysis technique with the help of SPSS 22 statistic program. The regression formula found in this research was Y=0.941 +0.221x1 +0.305x2 +0.522x3. The analysis result Showed that non-financial reward and punishment did not gave a significant effect on job loyalty through job satisfaction this indicates that non-financial reward and punishment can affect job loyalty positively but not significantly, directly non-financial reward and punishment gave a positive and significant effect on job loyalty by 48.1% and non-financial reward and punishment affect job satisfaction by 46% all of this indicates that the better the non-financial reward and punishment strategy implied in an organization the higher employee’s job satisfaction and loyalty will be.Keywords: non-financial reward, punishment, job satisfaction, job loyalty